Rural and remote dental care: Patient characteristics and health care provision. (27th May 2020) - Gardiner, Fergus W.; Richardson, Alice; Gale, Lauren; Bishop, Lara; Harwood, Abby; Lucas, Robyn M.; Strickland, Lorika; Taylor, Sandra; Laverty, Martin
Abstract: Objective: To describe the characteristics of patients who used the Royal Flying Doctor Service dental clinics and determine Royal Flying Doctor Service and non‐Royal Flying Doctor Service dental service provision in mainland Australia. Design: A prospective cohort study. Setting: All Royal Flying Doctor Service dental clinics located throughout rural and remote Australia. Participants: All patients who accessed an Royal Flying Doctor Service dental clinic from April 2017 to September 2018. Interventions: Royal Flying Doctor Service mobile dental clinics. Main outcome measures: Patient demographics and dental procedures conducted (by age, sex and Indigenous status); and the dental service provision and coverage (Royal Flying Doctor Service and non‐Royal Flying Doctor Service) within mainland rural and remote Australia. Results: There were 8992 patient episodes comprising 3407 individual patients with 27 897 services completed. There were 920 (27%) Indigenous and 1465 (43%) non‐Indigenous patients (n = 1022 missing ethnicity data). The mean (SD) age was 31.5 (24.8) years; the age groups 5‐9 years and 10‐14 years received 17.6% and 15.1% of the services, respectively. There were 1124 (33%) men and 1295 (38%) women (n = 988 with missing sex data). Women were more likely (all P  < .05) to receive preventive services, diagnostic services, restorative services, general services, endodontics and periodontics. Men were more likely (both P  < .05) to receive oral surgery and prosthodontics. There are many rural and remote people required to travel more than 60 minutes by vehicle to access dental care. Conclusion: Without increasing dental provision and preventive services in rural areas, it seems likely that there are and will be unnecessary oral emergencies and hospitalisations.